WILLINGNESS TO COMMUNICATE IN TASK-BASED INSTRUCTION: ANALYSIS OF FLUCTUATION IN DYNAMIC SYSTEM - Yohanes Kurniawan; Eka Fadilah; Nopita Trihastutie (Edulitics (Education, Literature, and Linguistics) Journal, 2018)
The present study aims at investigating the fluctuation of learners’ willingness to communicate in three communicative tasks: Dictogloss, Jigsaw-Game, and problem solving. We focus on learners’ L2 WTC in the classroom context seen from dynamic system theory. Six Indonesian undergraduate learners of English Department comprising linguistic features proficiency and motivational levels were elected as participants by encountering them in a three-subsequent-task performances. Concurrent assesment and Stimulated recall, and in-depth interview were used to investigate learners’ WTC during the task performances in the classroom interaction. The former used WTC-metric by asking the participants to provide scores on five-minute-interval of total 60 minutes task performances, while the two latters used video-taped as stimulus to confirm learners’ interaction in the classroom. The results reveal that learners’ WTC fluctuate during three task performances in conjunction with variables that interplay and interconnect one to another. Additionally, some factors provoking either learners’ willingness or unwillingness to communicate are discussed further.